Studies on the Environmental Stress of the Genotypes of Winged Bean [Psophocarpus tetragonolobus (L.) DC.] : their Productivity and Micro-structural Differences - Ray, Sunanda; Sinhababu, Amalendu; Tah, Jagatpati (International Journal of Bio-resource and Stress Management, 2023)
Ten genotypes of winged bean [Psohocarpus tetragonolobus (L.) DC.] were procured from National Bureau of Plant Genetic Resource (NBPGR), New-Delhi for carrying out PhD programme of the first author in the Department of Botany, Burdwan University. These ten genotypes were grown at the Crop Research Farm (CRF) under this department following Randomized Block Design (RBD) in four replications in the month of May, 2011. Uniform agronomic measures were provided for the proper growth and development of the crop. In general, the legume crop like winged bean does not grow well during rainy season. If so, abundance of abnormalities are noticed in the standing crop. But, it could survive easily by agronomic management in the rainy season without showing any gross abnormalities. Various agro-metrical characters viz. (i) plant height (cm),(ii) branches plant-1 (no.), (iii) days to initiation of flower bud (d), (iv) appearance of first green pod (d), (v) fruits plant-1 (no. at 50% flowering stage), (vi) podsplant-1 (no. at pre-harvesting period), (vii) weight of 100 grains (g), (viii) seed weight plant-1 (g) and (ix) yield plant-1 were observed and recorded properly till harvesting. Besides these, a few biochemical parameters viz. (i) soluble carbohydrate, (ii) insoluble carbohydrate, (iii) protein, (iv) chlorophyll content, (v) DNA contents and (vi) RNA contents were also measured for assessing variations of biochemical components of the genotypes. This might be either due to good health of the crop i.e. uniform agronomic management technology or potentiality of genotypes which were grown at the location. The analyses of variances like component of variances, genotypic coefficient of variation, phenotypic coefficient of variation and their heritability have been calculated following Singh and Chaudhary (1985).